PRODUKTIVITAS LAHAN, KOMPETISI, DAN TOLERANSI DARITIGA KLON UBIJALAR PADA SISTEM TUMPANG SARI DENGAN JAGUNG - Paulus, Jeanne Martje (Universitas Sam Ratulangi, 2005)
ABSTRACT Paulus, J.M. 2005. Land Productivity, Competition, and Tolerance of Three Sweet Potato Clones Planted as Intercroping with Maize. Eugenia 11 (1): 1-7. A field experiment was conducted in Cikeumeuh Experimental Garden of Food Crop Biotechnology Research Station (BAUTBIO) Bogor to study Land Equivalent Ratio (LER), Competition Ratio (CR), and Stress Tolerance (TOL) of sweet potato and maize. The highest tuber yiled of sweet potato was 16,83 ton ha-[1] gained by CIP-2 at 100 cm planting distance of maize and the highest maize yiled was 4,50 ton ha-1 Cangkuang in intercropping with Cangkung clone. The LER, CR, and TOL, CIP-2 and SQ were suitable for intercrops at all planting distance but Cangkuang was not suitable for intercrops with maize. Keywords: Ipomoea batatas, clon, intercroping [1] Jurusan Budidaya Pertanian, Fakultas Pertanian UNSRAT Manado, 95115